Child labour in global society - Close, Paul (Sociological studies of children and youth, 2014)
This book presents a novel study of children's compulsory productive educational labour in modern and modernizing societies under globalization, and the implications for such matters as childrens everyday lives, relationships and rights, international legal instruments, relevant analytical notions (including slavery), and sociological analysis.